Full-endoscopic removal of third ventricular colloid cysts: technique, results, and limitations - Unal, Tugrul Cem; Sencer, Altay; Dolas, Ilyas; Gulsever, Cafer Ikbal; Sahin, Duran; Dolen, Duygu; Ozata, Musa Samet; Ozturk, Metehan; Aras, Yavuz; Aydoseli, Aydin (Frontiers in Surgery, 2023)
Introduction: Colloid cysts (CCs) are rare benign lesions that usually arise from the roof of the third ventricle. They may present with obstructive hydrocephalus and cause sudden death. Treatment options include ventriculoperitoneal shunting, cyst aspiration, and cyst resection microscopically or endoscopically. This study aims to report and discuss the full-endoscopic technique for removing colloid cysts. Materials and Methods: A 25-angled neuroendoscope with an internal working channel diameter of 3.1 mm and a length of 122 mm is used. The authors described the technique of resecting a colloid cyst by a full-endoscopic procedure and evaluated the surgical, clinical, and radiological results. Results: Twenty-one consecutive patients underwent an operation with a transfrontal full-endoscopic approach. The swiveling technique (grasping the cyst wall and rotational movements) was used for CC resection. Of these patients, 11 were female, and ten were male (mean age, 41 years). The most frequent initial symptom was a headache. The mean cyst diameter was 13.9 mm. Thirteen patients had hydrocephalus at admission, and one needed shunting after cyst resection. Seventeen patients (81%) underwent total resection; 3 (14%), subtotal resection; and 1 (5%), partial resection. There was no mortality; one patient had permanent hemiplegia, and one had meningitis. The mean follow-up period was 14 months. Conclusion: Even though microscopic resection of cysts has been widely used as a gold standard, successful endoscopic removal has been described recently with lower complication rates. Applying angled endoscopy with different techniques is essential for total resection. Our study is the first case series to show the outcomes of the swiveling technique with low recurrence and complication rates.